2011
DOI: 10.1002/ibd.21416
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in Crohnʼs Disease patients treated with infliximab: A long-term multicenter matched pair study

Abstract: The frequency of neoplasia was comparable in an adult population of CD patients treated or not with infliximab, matched for clinical variables and followed up for a median of 6 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 32 publications
4
25
0
Order By: Relevance
“…For instance, the risk of developing lymphoma and non-melanoma cutaneous tumors is increasing over time under azathioprine treatment. [15][16][17][18] Trials investigating the consequences of immunosuppressive or biological therapy withdrawal 12,14,29 have defined the background relapse risk and related factors. The time limit of four years suggested to the panellists' assessment was set in analogy to studies evaluating the outcome after withdrawal of azathioprine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the risk of developing lymphoma and non-melanoma cutaneous tumors is increasing over time under azathioprine treatment. [15][16][17][18] Trials investigating the consequences of immunosuppressive or biological therapy withdrawal 12,14,29 have defined the background relapse risk and related factors. The time limit of four years suggested to the panellists' assessment was set in analogy to studies evaluating the outcome after withdrawal of azathioprine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, safety issues such as infections and neoplasia in the context of long-term immunomodulatory and anti-TNF, mostly in the case of combination therapy, 4 are still of significant concern to both patients and physicians. Hence, higher risks of lymphoproliferative disorders [15][16][17] and non-melanoma skin cancer 18 have been documented in patients receiving long-term immunosuppressive drugs. 19 Furthermore, the significant cost of anti-TNF treatment is of increasing concern in the current climate of budget constraints in healthcare systems.…”
Section: Introductionmentioning
confidence: 99%
“…45 However, Infliximab must be administered systemically and its use is limited owing to serious side effects, including acute or delayed infusion reactions, leukopenia, serious infection, antichimeric antibody formation, increased risk of malignancy and lymphoma as well as psoriasis. [46][47][48][49][50][51][52][53] Thus, there is an unmet need for a carrier system capable of specifically and exclusively delivering drugs to the inflamed regions for a prolonged period of time. Such a system could significantly reduce side effects of existing, otherwise effective, treatments.…”
Section: Micheliolide and Colitis-associated Cancer E Viennois Et Almentioning
confidence: 99%
“…Though it is now firmly established that thiopurines are associated with an increased lymphoma risk and a nonmelanoma skin cancer risk, similar associations with TNF-α inhibitors have been less consistent [55,60,61,62,63]. Subgroup analysis of 9 randomized clinical trials on infliximab, adalimumab and certolizumab pegol in IBD as well as a meta-analysis of 10 randomized clinical trials on infliximab use in IBD, showed no increase in lymphoma risk; likewise, data from the TREAT database on infliximab use in IBD have been unable to identify any increased risk of lymphoma development [55,64,65].…”
Section: Concerns About Biological Agents Regarding Infections and Mamentioning
confidence: 99%
“…Most of the patients who developed lymphomas were on combination therapy with thiopurines, and it is therefore currently not clarified if the increased lymphoma risk can be attributed to the TNF-α blockers, the thiopurines or both. The risk of developing solid tumors in patients in anti-TNF-α therapy is poorly investigated in CD but seems to not actually be greater [61]. …”
Section: Concerns About Biological Agents Regarding Infections and Mamentioning
confidence: 99%